Novel RP-HPLC-PDA Approach for Efficient Simultaneous Quantification of Imipenem, Cilastatin and Relebactum in Bulk Drug and Injection Dose Forms - Ponnekanti, Krishnaphanisri; Sunitha, K. (Asian Journal of Chemistry, 2021)
In this investigation, a highly reliable, precise, stability indicating, specific and selective RP-HPLC approach with photodiode array detection (RP-HPLC-PDA) was established to determine simultaneously imipenem, cilastatin and relebactum in bulk drug and injection dose forms. Chromatographic separation of imipenem, cilastatin and relebactum was achieved via using C18 XTerra column and a mobile phase poised of acetonitrile and 0.1 M dipotassium hydrogen phosphate buffer (4.5 pH, set with 0.1% orthophosphoric acid) at 45:55 (v/v) ratio with a flow stream of 1 mL/min. The photodiode array detector was fixed at wavelength 245 nm and quantifications of imipenem, cilastatin and relebactum were based on assessing their peak response areas. Good linearity was detected in target range concentrations of 250-750 μg/mL (imipenem and cilastatin) and 125-375 μg/mL (relebactum). The precision (standard variation percentage) was between 0.141% and 0.257%. Accuracy (%assay nominal) determined was between 99.144% and 99.638%. The validated RP-HPLC approach was applied to Recarbio injection dose evaluating imipenem, cilastatin and relebactum content with no interference encountered from the injection dose inactive ingredients. Imipenem, cilastatin and relebactum were subjected to forced conditions like 30% peroxide, 0.1 N NaOH, sunlight, 0.1 N HCl and 60 ºC. Imipenem, cilastatin and relebactum were effectively separated, quantified and resolved from the degradants generated in forced conditions.